Prematuritas Berdampak Terjadinya Hiperbilirubinemia Pada Neonatus Di Perinatologi RS Dr. Hafiz Cianjur - Ayi Nurlatifah; Weslei Daeli; Bambang Suryadi (Pusat riset dan Inovasi Nasional, 2024)
Prematurity is the birth or delivery of a baby that occurs between 20 weeks gestation to less than 37 weeks. About 25-50% of newborns suffer from jaundice in the first week. Hyperbilirubinemia in infants less months has a higher incidence rate. These developmental and clinical phenomena contribute to a greater degree and duration of neonatal hyperbilirubinemia in premature infants. Objective: to analyze the relationship of prematurity with hyperbilirubinemia in neonates at Perinatology Dr. Hafiz Cianjur Hospital. Method: The design used is quantitative observational with a cross-sectional approach. Samples were taken as many as 60 neonates using total sampling techniques. The research data was taken using medical record sheets in October – December 2023. Results: After analyzing the data was tabulated using a chi square test with a meaning level of 0.05. The results showed Prematurity (51.7%) as many as 31 neonates gestation period 31-36 weeks and Hyperbilirubinemia (86.7%) as many as 52 neonates in the severe category. The results of statistical testing obtained a significancy value of 0.003. Based on the results of p value < 0.05. Conclusion: it can be concluded that there is a relationship between prematurity and hyperbilirubinemia in neonates in Hospital Perinatology.